Der erste Buchdruck in Tübingen (1498-1534) : Ein Beitrag zur Geschichte der Universität - Steiff, Karl (European History and Culture - Book Archive pre-2000., 1963)
Supplemented by additions published in the Zentralblatt für Bibliothekswesen 1887, 1889, 1896. Describes 161 genuine Tübingen imprints, 18 dubious and 57 apocryph imprints as well as 54 books printed outside of Tübingen.